Galathea nasimae, new name for Galathea keijii Tirmizi & Javed, 1993, preoccupied by Galathea keijii Karasawa, 1993 (Decapoda: Anomura: Galatheidae) - Karasawa, Hiroaki (Zootaxa, 2019)
The name, Galathea keijii, was given to a Miocene fossil species of squat lobster from Japan by Karasawa (1993: 39, pl. 6, figs. 1, 2, 3, 10). In the same year, the name, Galathea keijii, was established for a living species from the Andaman Sea and Arabian Sea (Tirmizi & Javed 1993: 50, fig. 22). Therefore, both names are homonymous. The description of Karasawa was published in the Bulletin of the Mizunami Fossil Museum, no. 20, which, on the inside back cover states the date of publication as December 25, 1993. The description of Tirmizi & Javed was published in “Indian Ocean galatheids (Crustacea: Anomura)” by the Marine Reference Collection and Resource Centre, University of Karachi. This work was published in 1993 but the day and month of publication were not cited in the publication. In the absence of evidence to the contrary, the date of publication for “Indian Ocean galatheids (Crustacea: Anomura)” is deemed to be the last day of 1993, by application of Article 21.3.2 of the International Code of Zoological Nomenclature (ICZN 1999: 20). As such, application of Article 52 on the principle of homonymy of the International Code of Zoological Nomenclature (ICZN, 1999: 56) shows that Galathea keijii Karasawa, 1993, takes precedence over Galathea keijii Tirmizi & Javed, 1993. In accordance with Article 60 on the replacement of junior homonyms (ICZN 1999: 62, 63) a new replacement name, Galathea nasimae, is here proposed for Galathea keijii Tirmizi & Javed, 1993. It is dedicated to the late Dr. Nasima M. Tirmizi (Marine Reference Collection and Resource Centre, University of Karachi).